Morlachs, or Slavs from Dalmatia in French encyclopedias and dictionaries of the 18th and 19th century - Sajkowski, Wojciech (Poznańskie Studia Slawistyczne, 2018)
The Western view of the Balkans is, according to many researchers, synonymous with a stereotypical approach and ignorance regarding the history and culture of the nations inhabiting the Balkan Peninsula. The controversies could even refer to the names of individual Balkan communities that were and still are understood very differently. One example of such ambiguity is the name “Morlachs” i.e. “Black Vlachs”, which in reality was used to describe the Slavs of Dalmatia. This paper investigates the abovementioned issue on the example of the French encyclopedic sources, which are representative of the times in which they were created, as they were synthetic, and were intended for a wide audience. The form of the encyclopedic definition assumed synthesis, the gathering and summarizing the existing information. However, the French dictionaries and encyclopedias in the 18th and 19th century were not really able to synthesize known information about Dalmatian Slavs called by the name of Morlachs. Besides few exceptions, the explanations given by the dictionaries were imprecise, sometimes erroneous, referring to the past rather than to the present. In the light of the above, the statement that the French Enlightenment was one of the foundations on which the later stereotypical image of the Balkans emerged, seems justified.